Exploring Corporate Governance and Sustainable Performance in ASEAN: A Bibliometric Insight into Firm Performance - Sayuti, Alfian (Lembaga Penerbitan Unversitas Esa Unggul, 2025)
This Study conducts a comprehensive bibliometric analysis to explore the relationship between corporate governance, sustainable performance, and firm performance within the ASEAN region. By employing bibliometric tools, the research maps trends, influential publications, and intellectual structures in this field, focusing on how these concepts have evolved in academic literature over time. Key themes and co-citation networks are identified, providing insights into how corporate governance and sustainability are discussed concerning firm performance metrics both financial and market performance. The study reveals gaps and future research opportunities in this area, offering valuable guidance for researchers and practitioners in understanding the role of governance and sustainability practices in enhancing firm performance. The findings have implications for both scholars and policymakers aiming to foster sustainable economic growth in the ASEAN region.